2018
DOI: 10.3382/ps/pey061
|View full text |Cite
|
Sign up to set email alerts
|

Changes in hormone profiles, growth factors, and mRNA expression of the related receptors in crop tissue, relative organ weight, and serum biochemical parameters in the domestic pigeon (Columba livia) during incubation and chick-rearing periods under artificial farming conditions

Abstract: The present study was conducted to determine the changes in concentrations of hormones and growth factors and their related receptor gene expressions in crop tissue, relative organ weight, and serum biochemical parameters in male and female pigeons during incubation and chick-rearing periods under artificial farming conditions. Seventy-eight pairs of 60-week-old White King pigeons with 2 fertile eggs per pair were randomly divided into 13 groups by different breeding stages. Serum prolactin and insulin-like gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 75 publications
2
23
0
Order By: Relevance
“…Intestinal adaptation in different breeding stages was speculated to be regulated by specific hormones ( Baksheev and Fuller, 2000 ), such as glucocorticoids, cortisol, and triiodothyronine, which were already found to affect the digestive enzymes in animals ( Chapple et al., 1989 ; Khangembam et al., 2017 ). Our previous study showed that the prolactin concentration rapidly reached the peak value in both sexes on the first day of chick-rearing, but the estradiol concentration in female pigeons remained low until the late chick-rearing period ( Xie et al., 2018 ). Whether digestive enzymes in pigeons are influenced by these hormones warrants further investigation.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…Intestinal adaptation in different breeding stages was speculated to be regulated by specific hormones ( Baksheev and Fuller, 2000 ), such as glucocorticoids, cortisol, and triiodothyronine, which were already found to affect the digestive enzymes in animals ( Chapple et al., 1989 ; Khangembam et al., 2017 ). Our previous study showed that the prolactin concentration rapidly reached the peak value in both sexes on the first day of chick-rearing, but the estradiol concentration in female pigeons remained low until the late chick-rearing period ( Xie et al., 2018 ). Whether digestive enzymes in pigeons are influenced by these hormones warrants further investigation.…”
Section: Discussionmentioning
confidence: 96%
“…Our results showed that pancreatic amylase activity gradually decreased from I4 to R1 but then recovered to the beginning level in the late chick-rearing period. Pigeon serum glucose concentration was stable from egg incubation to chick rearing ( Xie et al., 2018 ), but hepatic glycogen content was reported to decrease significantly during the incubation period and then recovered when feeding nestlings ( Wan et al., 2018 ). In addition, our present study indicated that the activities of maltase and sucrose in mucosa also maintained a relatively lower level from I17 to R1.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations